Gall bladder tuberculosis: a rare entity - Lakhey, P; Shrestha, ML; Sayami, G; Khakurel, MP (Journal of Institute of Medicine Nepal, 2007)
Background: Though tuberculosis is common in other parts of the body, gall bladder tuberculosis is rare. We report a case of gall bladder tuberculosis managed in our institution. Case Report: A 42 year old lady presented with right upper quadrant pain associated with fatty meal intolerance for one month. The pain was relieved by antispasmodics. Her liver function test was normal. Ultrasonogram of abdomen revealed, thick wall gall bladder with solitary stone in the gall bladder. Retrograde subtotal cholecystectomy was done. The histopathology report of the gall bladder revealed granulomatous cholecystitis suggestive of tuberculosis. Key words: Gall bladder, Tuberculosis, Granulomatous cholecystitis. The full text of this paper is available at Journal of Institute of Medicine website